A report on metal additive manufacturing materials study - Yap, Wei Hao (Nanyang Technological University, 2023)
Additive Manufacturing (AM) has been gaining popularity and is constantly developing and advancing, which are mainly due to its advantages of being able to produce complex parts with high accuracy and precision. This report looks into AM categories like Directed Energy Deposition (DED) and Powder Bed Fusion (PBF), as well as Selective Laser Melting (SLM), which falls under the PBF category. Parts produced using SLM tend to have higher strength compared to their traditionally manufactured parts, as the material is melted and cooled rapidly due to the process. Fatigue and tensile testing was conducted on specimen extracted from a 316L Stainless Steel part produced using SLM. Yield Strength of the material were obtained from tensile testing and are then used for fatigue testing. Results are tabulated and plotted onto a S-N Curve and the specimen used are then analysed at their point of fracture.